WTO: As an Instrument of Dispute Settlement in the International Trade - Bajpai, Chitra; Malik, Priyanka; Krishnan, Chitra; Sahai, Seema; Goel, Richa; Singh, Gurinder (International Journal of Engineering and Technology, 2018)
The World Trade Organization is a platform which is primarily responsible for the rules and regulation related to the world trade for the member nations. This research paper is an effort to measure the effectiveness of the WTO as a Dispute Settlement Body (DSB). In relation to that the first objective of the research paper is to understand the nature of the International Trade Dispute among the member nations. The second objective of the research paper is to analyze certain International Trade Disputes which were reported to the WTO. The third objective of the research paper is to find out some common features among the analyzed cases.Â Â Â